Giant cell arteritis-where did we go wrong? - Devaraj, Navin Kumar (2019)
Giant cell arteritis, or also known as temporal arteritis is one of the rheumatological condition that need an urgent diagnosis. This is to prevent its most devastating complication, i.e. bilateral irreversible blindness. This case report will look at a case of a 60 year old man who had severe headache for 2 days that resulted in permanent blindness.